(untitled) (Journal of Medicine, 2022)
Background: Around a million FDMNs have settled in Cox’s Bazar, the southeast coastal district ofBangladesh. The geographically proximate country of Rakhine state of Myanmar following armed conflictin this area in August 2017 and created a unique humanitarian crisis. It is important to know the currenthealth status of FDMNs because, without this information, equal and equitable health service provision isnot possible. So, we conducted this study to explore the common health problems of FDMNs residing incamps of Cox’s Bazar, Bangladesh. Method: This descriptive observational study was conducted from January 2018 to July 2019 at Cox’sBazar Medical College Hospital, Cox’s Bazar which first prioritized referred tertiary hospitals for FDMNs. Result: Among study FDMNs, Age ranges from 3 months to 97 years with a median age of 40 (25-60) years andmale to female representatives were almost equal (51.6% male and 48.4% female). Majority of the male werefarmers (engaged in agriculture, livestock and fish farming) and the females were house makers. One third ofthe primary respondents have formal education (i.e. religious education) in Myanmar. More than 30% of theparticipants reported having H/O recent death of family members in Myanmar with a median number of twomembers due to recent violence. 37% FDMNs were malnourished out of them 14.7% were severe. BCG scarmarks were found in 70% and only 40.7% were vaccinated with other vaccines in under five children.75.4%FDMNs were dependent on unqualified village doctors” for treatment. The most common NCD among theFDMNs people were COPD, DM, and HTN with risk factor tobacco use and frequent betel nut chewing.Chronic liver disease with underlying hepatitis C or Hepatitis B infection, HIV and TB were more common.Nearly one third FDMNs were clinically anemic. 42.9% of the participants reported do not won and use LLNin Myanmar. 73.2% FDMNs have knowledge about ORS use in diarrhea. Predominant diseases among admittedprimary respondents were CLD (15.7%) followed by COPD (13%), pregnancy complication and Injury (7.2%).Major causes of death in admitted FDMNs were COPD with its complication (25%) Cardiac disease (20%),CLD with Hepatic encephalopathy (15%), CNS infection and Septic shock (10%). Conclusion: This study identifies common health problems of the FDMN also called Rohingya refugeesin Bangladesh. FDMNs in Bangladesh are under significant health risks and necessary to scale up targetedhealth care policy and improvement of local GOB and non-Government health care facilities for them. J MEDICINE 2022; 23: 13-19